Cataloguing Indian biota - Response - Chavan, V.; Watve, A. V.; Rane, N. S.; Krishnan, S. (Current Science, 2005)

IndCollections: biological specimens in Indian collections - Chavan, V.; Rane, N. S.; Ghate, H. V.; Krishnan, S. (Current Science, 2005)

R&D spending patterns of global firms - Bowonder, B.; Racherla, J. K.; Mastakar, N. V.; Krishnan, S. (Research-Technology Management, 2005)
R&D spending by the top 320 companies in 2004 was US\$ 331 billion. The R&D intensity of these globalfirms has decreased marginally, as there was a decrease in R&D spending by pharmaceutical firms. R&D spending as a percentage of sales is the highest in the biotechnology industry followed by pharmaceuticals and network communications. At the same time, more firms are seeking to acquire intellectual assets from external sources. Managing intellectual assets will require competence to integrate external and internal knowledge assets so that innovation efficiency can go up while idea-to-market time goes down and product pipelines get richer.
Keywords: distributed innovation; globalization; R&D spending

Who patented what in 2004 - Bowonder, B.; Krishnan, S.; Mastakar, N. V. (Research-Technology Management, 2005)

Harvesting chemical information from the Internet using a distributed approach: chemxtreme - Karthikeyan, Muthukumarasamy; Krishnan, S.; Pandey, A. K.; Bender, Andreas (Journal of Chemical Information and Modeling, 2006)
{The Internet is a comprehensive resource of chemical information which is at the same time largely unstructured. It provides a wealth of scientific information such as experimental data and requires a suitable automated data mining and analysis tool for its meaningful exploration. The Java based software presented here, ChemXtreme, is developed for harvesting chemical information from the Internet employing the Google API in combination with a distributed client/server text analysis architecture based on JavaRMI. It represents the first and until now the only toolkit for automated structured data retrieval from the Internet which is itself open source. ChemXtreme employs the ``search the search engine''
Keywords: calcination; clinker; one-dimensional model; rotary cement kiln

Distributed chemical computing using chemstar: an open source java remote method invocation architecture applied to large scale molecular data from pubchem - Karthikeyan, Muthukumarasamy; Krishnan, S.; Pandey, Anil Kumar; Bender, Andreas; Tropsha, Alexander (Journal of Chemical Information and Modeling, 2008)
present the application of a Java remote method invocation (RMI) based open source architecture to distributed chemical computing. This architecture was previously employed for distributed data harvesting of chemical information from the Internet via the Google application programming interface (API; ChemXtreme). Due to its open source character and its flexibility, the underlying server/client framework can be quickly adopted to virtually every computational task that can be parallelized. Here, we present the server/client communication framework as well as an application to distributed computing of chemical properties on a large scale (currently the size of PubChem; about 18 million compounds), using both the Marvin toolkit as well as the open source JOELib package. As an application, for this set of compounds, the agreement of log P and TPSA between the packages was compared. Outliers were found to be mostly non-druglike compounds and differences could usually be explained by differences in the underlying algorithms. ChemStar is the first open source distributed chemical computing environment built on Java RMI, which is also easily adaptable to user demands due to its ``plug-in architecture''. The complete source codes as well as calculated properties along with links to PubChem resources are available on the Internet via a graphical user interface at http://moltable.nel.res.in/chemstar/.